(untitled) (Bangladesh Journal of Zoology, 2022)
A study was carried out to determine the effectiveness of newly synthesized chemical ‘4-[3-(4-biphenylyl)-1, 6-dihydro-6-iminopyridazin-1-yl] butyronitrile hydro bromide against beanaphid, Aphis craccivora, under six treatments: T1 (20 ppm), T2 (40 ppm), T3 (60 ppm), T4 (80 ppm), T5 (100 ppm), and untreated control T6. Aphid numbers was peaked in January and it was zero in February. The best efficacy of administered doses was found in the T3 and followed by T5, T4, and T2, respectively. The aphid abundance in different weeks (F= 1.89; p<0.05) and the treated doses (F= 3.19; p< 0.02) were significantly varied among the plants. The aphid population showed a positive correlation with temperature in the T3 (r = 0.48) and T5 (r = 0.33) and a negative correlation in T1 (r = -0.32), T2 (-0.24), and T4 (-0.20), and untreated control T6 (- 0.24). Whereas, aphids were positively correlated with humidity in T3 (r = 0.46), T4 (r = 0.40), and T5 (r = 0.18) and negatively correlated in T1 (r = -0.32), T2 (r = -0.53), T4 (r = -0.40), and untreated control T6 (r = -0.52). The treated doses T4 and T3 produced the most vigorous fruits, while T1 produced the lowest. Bangladesh J. Zool. 50 (2): 261-272, 2022